Dentition and nutritional status of aged New Zealanders living in aged residential care. (30th July 2020) - van Kuijk, Maria; Smith, Moira B.; Ferguson, Catherine Anna; Kerse, Ngaire M.; Teh, Ruth; Gribben, Barry; Thomson, William Murray
Abstract: Background: Previous studies of the nutritional status of older individuals have used measures such as plasma vitamin and mineral levels, which can be difficult to interpret. The relationship between nutrition and dentition has been limited to studying exposures such as the number of posterior occluding pairs of teeth, edentulousness, and the number of natural teeth. Objectives: To investigate the association between dentition status and nutritional status in a national survey of older New Zealanders living in aged residential care facilities. Material and methods: Secondary analysis of clinical oral status and nutrition data collected in 2012 in New Zealand's Older People's Oral Health Survey. The validated Mini Nutritional Assessment short format was used to categorize participants as "normal nutritional status, " "at risk of malnutrition" or "malnourished." Results: Just under half of older New Zealanders living in aged residential care facilities were classified as either at risk of malnutrition or malnourished (with about one in sixteen in the latter category). The prevalence of malnutrition was higher among those in hospital‐level and psychogeriatric‐level care, as well as in those of high socioeconomic status. Individuals who were at risk of malnutrition had the most untreated dental caries and untreated coronal caries. Relative to their counterparts in nursing‐home‐level care, dentate individuals in hospital‐level care were 2.4 times—and those in psychogeriatric‐level care were 2.8 times—as likely to be malnourished or at risk of it. Conclusions: Just under half of the New Zealanders living in aged residential care were at risk of malnutrition or were malnourished. Greater experience of untreated dental caries was associated with a higher rate of being malnourished or at risk of it. Poorer cognitive function and greater dependency were important risk indicators for malnutrition.